KEY FACTORS FOR THE DEVELOPMENT OF RURAL E-COMMERCE IN VIETNAM BASED ON THE O2O MODEL - Nho Quyet, Tran; Ji Tong, Guang; Thi Thanh Hien, Nguyen; Nho Cuong, Tran (Journal of Forestry Science and Technology, 2021)
E-commerce has explosively developed, followed by the O2O model which has gradually affirmed its advantages in agricultural products trading, especially fresh specialties. The construction of rural e-commerce in Vietnam based on this model certainly seizes opportunities to promote local farm produces (specialties, diversities) in Vietnam to travel throughout the country, and go global, to develop TAM NONG Vietnam policy in the digital era. This research uses logistic regression and cross-sectional descriptive methods, aiming at shedding light on the key factor for the development of rural e-commerce in Vietnam based on the O2O model, which is a logistics management system, thereby evaluating and introducing solutions to apply the “The Last Kilometer” - a model of Chinese e-commerce as the basis for expanding rural E-commerce strategy in Vietnam. The results showed the key point of kick-start rural E-commerce in Vietnam is logistic management, which can be described by the following factors: transport systems, delivery time and location networks, the supermarket chain, automatic counters and professional employees’ attitudes. The results also confirmed that logistics management has an important role in the development of rural e-commerce in Vietnam according to the O2O model, and the application of the “the last Kilometer” solution of Chinese e-commerce is appropriate with the development trend of logistics in Vietnam.